Archaeological Source Study of the Golden Horde Nomads or Stagnation of Dialectics » - Vladimir Ivanov (Золотоордынское обозрение, 2016)
The author of this article aims to draw the attention of his colleagues – researchers of the history and archaeology of the Golden Horde – on the state of the source base on the culture of the nomadic Golden Horde population. In his view, currently the source base could be characterized as being in paradoxical situation. According to the data, which the author has at his disposal, so far 1179 burials of pagan nomads of the 13th–14th centuries were examined and for the most part published. This number is 1,2 times greater than the number of nomadic burials of the 10th–14th centuries, which G.A. Fedorov-Davydov described in 1966 and who developed a typology and chronology of nomadic medieval antiquities of Eastern Europe. This amount will increase by 2–3 times if we also take into account the Muslim burials. At the same time, discovered and studied nomadic burials of the 13th–14th centuries in the steppes of Eurasia for the most part are found in the steppes of Eastern Europe and they are virtually unknown in the east of the Eurasian Steppe – in the area of the historical “generator” of nomadic peoples. We can explain this paradox either by using the S.A. Pletneva’s concept about three stages of nomadism, according to which the first stage did not leave any archeological monuments, or by the sources lacuna caused by the reduced interest of researchers of eastern Eurasian steppe toward the steppe nomadic monuments of the Middle Ages. The absence of a truly empirical approach to the archaeology of the Golden Horde nomads causes the knowledge stagnation of their history and culture. This is manifested in the creation of narrative discourse understandable only to the meta-ontological perception: about the White Horde – an extensive state east of the Yaik / Ural River; about sedentarization of the Kipchaks in the Jochid Ulus; about autochthonous subbase of the nomads of the 13th–14th centuries in the Ural-Volga region, and the like.